The embodied carbon of paracetamol and the consumables associated with different routes of administration in pediatrics - Nicola Wilson; Caroline Dalton (The Journal of Climate Change and Health, 2024)
Background: The aim of this study was to estimate the embodied carbon of different formulations of paracetamol, its packaging and the consumables used in administration within pediatrics. Methods: A set dose of 750 mg was chosen to represent complex dosing seen in pediatrics and then two separate approaches to measuring the embodied carbon were taken. A top-down environmentally extended input-output analysis for the drug and a bottom-up approach using the emissions factors for the primary material was used for the packaging and consumables. Results: All oral methods of administration have the lowest embodied carbon when accounting for the drugs, consumables, and packaging. Conclusion: This study demonstrates how working across disciplines we can look for ways in which we can minimize the carbon cost of care. This study finds that when accounting for patient safety, acceptability within pediatrics and the embodied carbon, all non-IV methods are preferable.